How to prevent workplace incivility?: Nurses' perspective - Farahnaz Abdollahzadeh; Elnaz Asghari; Hossein Ebrahimi; Azad Rahmani; Maryam Vahidi (Wolters Kluwer Medknow Publications, 2017)
Background: Many articles have studied workplace incivility and its influence on outcomes, but very few have been conducted to assess how to prevent this issue. In this study, we aimed to determine how to prevent workplace incivility from the nurses' perspective. Materials and Methods: This was a qualitative study which was based on a conventional content analysis approach. Thirty four nurses (25 to 52 years old) from seven training hospitals in Tabriz, Iran were selected through purposive sampling. Thirty six semi-structured interviews and eight field notes were analyzed. Results: The data analysis revealed 417 codes, ten categories, three subthemes and one theme, that is, A Need for a Comprehensive Attempt. Attempt of organization, nurses, and public as subthemes are needed to prevent workplace incivility. Conclusions: The findings of the study indicated that a comprehensive and systematic attempt was needed to prevent incivility. Nurses should try to improve their skills; officials should try to show the real image and position of nurses and hospitals to the community.